2008
DOI: 10.1016/j.breast.2007.11.031
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic importance of triple negative breast carcinoma

Abstract: There is a current debate on whether triple negative breast carcinomas (estrogen receptor--ER-negative, progesterone receptor--PR-negative and HER2-negative) have a poor prognosis. Our aim in this retrospective study was to determine whether triple negative feature is a prognostic factor for disease-free survival (DFS) in 322 breast carcinoma patients, of whom 80 (24.8%) had triple negative tumor histology. In the multivariate analysis, tumor subgroup (triple vs non-triple, p<0.0001; hazard ratio [HR], 4.2; 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
61
4
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 22 publications
9
61
4
3
Order By: Relevance
“…Also, LRRFS, DFS and OS were similar for both groups. It is believed that factors like young age and poor differentiation of triple negative cancers contribute to their aggressive nature (Mersin et al, 2008;Kwan et al, 2009;Dawood et al, 2010). These factors have been shown to be independent predictors of outcome in breast cancer patients (Adami et al, 1986;Chung et al, 1996;Sidoni et al, 2003;Sharif et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Also, LRRFS, DFS and OS were similar for both groups. It is believed that factors like young age and poor differentiation of triple negative cancers contribute to their aggressive nature (Mersin et al, 2008;Kwan et al, 2009;Dawood et al, 2010). These factors have been shown to be independent predictors of outcome in breast cancer patients (Adami et al, 1986;Chung et al, 1996;Sidoni et al, 2003;Sharif et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Triple-negative tumours account for 10.6-29.5% of all breast cancers (8)(9)(10)(11)(12). As proven by the results of previous studies, standard treatment protocols used for breast cancer management have not yielded the expected successful results in this subgroup to date.…”
mentioning
confidence: 99%
“…TNBCs represent an important subtype of breast cancer as they have a lower recurrence-free and overall survival compared to receptor-positive disease, regardless of disease stage at time of diagnosis. 1,2 A large proportion of tumours arising in BRCA1 germline mutation carriers display a triple-negative phenotype and gene expression profiles of BRCA1-associated breast cancers are similar to those of TNBCs. 3 It has been suggested that TNBCs may harbour mutations in genes involved in the BRCA-associated DNA repair pathway [3].…”
mentioning
confidence: 99%
“…Multiple studies have shown that women with TNBC do not benefit from trastuzumab or endocrine therapy 1,41 and are associated with an adverse prognosis, with greater risk of recurrence even when treated with adjuvant chemotherapy. 42 Recent studies have shown that TNBC patients with germline BRCA mutations have a stronger response to treatment with DNA-damaging cytotoxic chemotherapies and poly(adenosine diphosphate)-ribose polymerase (PARP) inhibitors, which selectively target cells that are deficient in homologous recombination DNA damage repair.…”
mentioning
confidence: 99%